2021
DOI: 10.1001/jamanetworkopen.2020.37512
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hepatocellular Carcinoma Incidence and Risk Among Persons With HIV in the US and Canada, 1996-2015

Abstract: Key Points Question Has the incidence rate or risk for liver cancer among people with HIV increased with the widespread availability of combination antiretroviral therapy? Findings In this cohort study of 109 283 people with HIV in North America, the incidence rate of liver cancer increased between the early and modern combination antiretroviral therapy eras. People with HIV coinfected with hepatitis B virus and/or hepatitis C virus, those with higher HIV R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…This is largely in line with findings from previous reviews. 11 , 126 A higher proportion of smokers in PLHIV than that in the general population potentially contributed to a higher incidence of cancers induced by smoking (e.g., lung cancer). 92 A meta-analysis conducted in 2016 reported that the prevalence of current smokers in PLHIV in the US was around 54%, nearly doubling the figure in US adults (20-23%).…”
Section: Discussionmentioning
confidence: 99%
“…This is largely in line with findings from previous reviews. 11 , 126 A higher proportion of smokers in PLHIV than that in the general population potentially contributed to a higher incidence of cancers induced by smoking (e.g., lung cancer). 92 A meta-analysis conducted in 2016 reported that the prevalence of current smokers in PLHIV in the US was around 54%, nearly doubling the figure in US adults (20-23%).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Specific risk factors include viral infections caused by hepatitis B virus (HBV) and/or hepatitis C virus (HCV), chronic alcohol consumption, particular comorbidities or other conditions such as non-alcoholic fatty liver disease, nonalcoholic steatohepatitis, genetic hemochromatosis, coinfection with HBV/HCV, and HIV. 1,[8][9][10][11][12][13][14] Localized HCC is asymptomatic for much of its natural history. Nonspecific symptoms associated with more advanced HCC can include jaundice, anorexia, weight loss, malaise, and upper abdominal pain.…”
Section: Overviewmentioning
confidence: 99%
“…It is estimated, however, that up to 40% of children with coinfection develop HCC later in life. Recent data from a large north American cohort of adults living with HIV have shown an increased risk of developing HCC even in the absence of HBV, but with the exception of sporadic case reports, little is known about the association between perinatally-acquired HIV and HCC [ 87 , 88 , 89 , 90 ].…”
Section: Hepatopancreatic Disordersmentioning
confidence: 99%